Динаміка результативності змагальної діяльності кваліфікованих волейболістів (за показниками результативності в партіях гри) - Олійник, Михайло Олександрович; Дорошенко, Едуард Юрійович; Oliynyk, M. O.; Doroshenko, E. Yu. (My University, 2018)
В статті на матеріалах змагань на першість Запорізької області з волейболу проаналізовано динаміку результативності кваліфікованих волейболістів у партіях гри і розглянуто можливості використання цих показників для формування моделей результативності змагальної діяльності у волейболі. В роботі запропонована послідовність дій для аналізу результативності змагальної діяльності кваліфікованих спортсменів у волейболі. Розглянуто варіанти розвитку гри в партіях з огляду на динаміку результативності кваліфікованих волейболістів і розвиток гри в партіях. In the article, on the materials of competitions on the championship of the Zaporizhzhya region on volleyball, the dynamics of the performance of qualified volleyball players in game parties is analyzed and the possibilities of using these indicators for forming of the models of the effectiveness of competitive activities in volleyball are considered. In the work of the proposed steps for the analysis of the effectiveness of competitive activities of qualified athletes in volleyball. The paper considers the options for development of the game in the parties, given the dynamics of the productivity of skilled volleyball players and the development of the game in batches.It is shown that when analyzing and interpreting the performance of qualified volleyball players in individual batches, the values of the ratio of the points scored at the beginning of the batch (up to 8 points), in the middle of the batch (up to 16 points), at the end of the batch (25 points or more) to form models of competitive activity and to select appropriate means of correction. Determined that the total indicators of the effectiveness of skilled volleyball players regarding game development options in the parties indicate that the linear variants of development of the game in batches accounted for 60% of the cases (option 1 – 50% and option 5 – 10%) found that the formation of models that reproduce the dynamics of productivity of skilled volleyball players in lots of game accounts for 40% on the basis of six variants of development of game. Found that in the study of the dynamics of indicators of effectiveness of skilled volleyball players in the new game is defined as follows: option 1 the dynamics of productivity – 50%; option 3 – 20%; option 5 – 10%; option 7-10%; option 8-10%. It is established that the basis of the forming models of competitive activities taking into account the dynamics of the indicators of the effectiveness of skilled volleyball players appropriate to use variants of the development of the game. Thus, in 50% of cases, the team that won the advantage at the beginning of the party, the party of the fetters and the advantage received for victory in the party.
Dynamics of the effectiveness of competitive activities of qualified volleyball players (in terms of performance in batches).
Keywords: волейбол; визначення; результативність; кваліфікація; формування; модель; змагання; діяльність; volleyball; definition; performance; qualification; formation; model; competition; activity